Human rights for the third millennium / by M.Ponnaian, Panch Ramalingam and Rani Ponnaian - Ponnaian, M; Ramalingam; Ponnaian, Rani (Delhi, 2001)
This book presents a detailed sketch of innumerable upheavals which depict a lamentable catalogue of violations of exploitative outcry of barbaric atrocities, tyrannical autocracy, horrendous genocide, inhuman torture, hellish brutality, remorseless and heartless murders.
Keywords: Civil rights